Measurement of inclusive and dijet D* meson cross sections in photoproduction at HERA - Aaron, Francisc Dionisie; Hennekemper, Eva; Jung, Andreas Werner; Krüger, Katja; Lendermann, Victor; Pirumov, Hayk; Sauter, Michel David; Schöning, André; Schultz-Coulon, Hans-Christian; Urban, Klaus (The European physical journal. C, Particles and fields, 2012)
The inclusive photoproduction of D ∗ mesons and of D ∗-tagged dijets is investigated with the H1 detector at the ep collider HERA. The kinematic region covers small photon virtualities Q 2<2 GeV2 and photon-proton centre-of-mass energies of 100<W γp <285 GeV. Inclusive D ∗ meson differential cross sections are measured for central rapidities |η(D ∗)|<1.5 and transverse momenta p T (D ∗)>1.8 GeV. The heavy quark production process is further investigated in events with at least two jets with transverse momentum p T (jet)>3.5 GeV each, one containing the D ∗ meson. Differential cross sections for D ∗-tagged dijet production and for correlations between the jets are measured in the range |η(D ∗)|<1.5 and p T (D ∗)>2.1 GeV. The results are compared with predictions from Monte Carlo simulations and next-to-leading order perturbative QCD calculations.
Im Titel wird "ast" als griechischer Buchstabe dargestellt und steht hoch
H1 Collaboration: F.D. Aaron, E. Hennekemper, A.W. Jung, K. Krüger, V. Lendermann, H. Pirumov, M. Sauter, A. Schöning, H.-C. Schultz-Coulon, K. Urban [und weitere]
Gesehen am 08.11.2018